Grenzöffnungen in geteilten Städten — Simulationen der Folgen für die Stadtstruktur1 - Wagner, Wolfgang (Raumforschung und Raumordnung | Spatial Research and Planning, 2005)
Poland's joining the EU rises the question of the effects the opening of borders has on formerly separated cities. As consequence of the fall of the Berlin wall Häußermann and Kapphan (2000) observed the development of segregation. This contribution, by means of microeconomic simulations of the housing market, examines whether their findings are systematic or rather an empirical exception. Under a perfect price mechanism, segregation already arises within the divided city and remains even after the border has been opened. In case of limited pricing, segregation can be avoided as long as the city is divided but not after its unification.